Hepatitis C genotype 1a replicon improved through introduction of fitness mutations. (April 2012) - Voitenleitner, Christian; Bechtel, Jill; Arfsten, Ann; Hamatake, Robert
The use of subgenomic replicon systems has long been a valuable screening tool for the discovery of small molecule antivirals against Hepatitis C virus. While genotype 1a replicon systems have been widely used in stable systems, use in transient assays has been hampered by low signal. Here we describe the generation of a more robust genotype 1a (H77) replicon through the introduction of two fitness mutations, NS4A-K1691R and NS4B-E1726G, for use in transient transfections. While these mutations significantly improved the signal to noise ratio, leading to more robust data, they have no effect on the potency of tool compounds against various targets of HCV, thereby making this new system a powerful tool for screening of compounds against the genotype 1a replicon.